Heritage and tourism processes in the legitimization of unequal landscapes - Pérez Winter, Cecilia Verena (Sociedade & Natureza, 2017)
Several authors have pointed out how the logic of capitalist development generates socio-economic inequalities, which are embodied in the territory. It creates, legitimates and reproduces socio-spatial injustices; which can be consolidated by heritage valorization and tourist commodification processes. Both select and prioritize an area through actions and speeches that justify its preservation. In this context, we consider the identification of the historic centres from those processes. To this end, we propose to examine San Antonio de Areco city, located in the homonymous district in the province of Buenos Aires (Argentina). We are interested in analyzing the territorial implications of these processes that enables the legitimation of the historic centre as a landscape of “privilege”.